THE EFFECT OF USING WHATSAPP AS A LEARNING TOOL ON STUDENTS’ WRITING ABILITY AT MA LABORAN - Anggraini, Desti; Taridi, Muhammad; Azizah, Nur (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2020)
The purpose of this survey was to determine how students at MAN 1 Tanjung Jabung Barat perceive reading texts. This survey-based research is quantitative in nature. This study's participants were eleventh-grade pupils at MAN 1 Tanjung Jabung Barat. In this study, simple random sampling was used to select 50 students, or 29% of the total population, from XI IS I and XI IS II classes where 63 pupils were taught by the same teacher. In terms of data acquisition methods, a questionnaire was used. The analysis of the utilised data is a quantitative analysis. The results indicated that 80% of MAN 1 Tanjung Jabung Barat students' perceptions of reading texts fell into the category of